Marshal Stability Analysis of Asphaltic Concrete: A comparative strength based investigation of KP Pakistan Principal Aggregate Quarries - Kashif Alam; Tasaddaq Younas; Muhammad Nadeem; Waseem Younas; Sachal Khan; Arshad Khan (Journal of ICT, Design, Engineering and Technological Science, 2021)
Various types of hot asphalt (mixture of mineral aggregate and bituminous binder–bituminous mixture) are used in the construction of flexible pavements, depending on the project requirements, to ensure optimal use of the asphalt. From all available asphalts, each country uses a combination of those that are considered to be the most appropriate to their climatic and traffic conditions. Asphalts are characterized by the particle size distribution of the aggregate mixture. Theoretically, there are unlimited types of asphalts, namely, from asphalts consisting only of almost single-sized coarse aggregates to mixtures consisting only of fine aggregates (sand). The goal of bitumen laboratory testing is to describe its qualities, determine its appropriateness, and forecast its behaviour over the course of the pavement's service life. All technological, mechanical, rheological, physical, and chemical attributes are included in the term typical properties. The purpose of the report is to collect aggregate samples from Malakand, Dara Adam Khel, Basai, and Karak quarries and to compare its Physical and Mechanical Properties with Margalla aggregate by using the Marshall Method of design for asphalt concrete.